Zakah as Deductible for Taxable Income: A Macroeconomic Perspective - Akhmad Akbar Susamto (Jurnal Iqtisad, 2003)
Zakah is a very basal religious service and closely interconnected with both transcen-dental and social aspects of human life. According to Islamic rules, zakah is imposed on every soul (zakah al-fitr) and certain properties meeting the standardized measure (zakah al-maal). Collected zakah is hereinafter distributed to the poor, the needy, the people em-ployed to administer zakah, and the people whose hearts are made to embrace Islam, the people in bondage, the people twined by debt, the fighters in the cause of Allah, as well as the wayfarers. In Zakah Management Act No. 38/1999 mentioned, that zakah which have been bestowed to Badan Amil Zakah or Lembaga Amil Zakah (i.e. government and non-government bodies for the collection of zakah respectively) will be considered as deducti-ble for one’s taxable profits or incomes. Likewise, in Act No. 17/2000 contended that zakah of income can be considered as deductible for one’s taxable incomes. With a few appropri-ate assumptions, we can prove that the application of zakah as deductible for one’s taxable incomes will have several impacts on the economy. Aggregate consumption will increase, saving will decrease, investment criterion will change, and national income as a whole will finally enlarge. Government is therefore suggested not to hesitate to execute the Zakah Consciousness Movement.